2017
DOI: 10.4274/tjh.2016.0123
|View full text |Cite
|
Sign up to set email alerts
|

Could Neutrophil CD64 Expression Be Used as a Diagnostic Parameter of Bacteremia in Patients with Febrile Neutropenia?

Abstract: Objective:The aim of this study is to investigate if neutrophil CD64 expression in febrile neutropenia patients could be used as an early indicator of bacteremia.Materials and Methods:All consecutive patients older than 18 years of age who had developed febrile neutropenia episodes due to hematological malignancies were included in the study. Those patients who had significant growth in their blood cultures constituted the case group, while those who had febrile neutropenia without any growth in their cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…N. Efe Iris studied adult patients and showed that the sepsis group had an average nCD64 index of 8006 molecules bound/cell, significantly higher than the control group (average nCD64 of 2786 molecules bound/cell). The cut-off value of nCD64 of 2500 molecules bound/cell is considered to have diagnostic value for sepsis in adults, with a sensitivity of 94.1% [7]. P.C.…”
Section: Discussionmentioning
confidence: 99%
“…N. Efe Iris studied adult patients and showed that the sepsis group had an average nCD64 index of 8006 molecules bound/cell, significantly higher than the control group (average nCD64 of 2786 molecules bound/cell). The cut-off value of nCD64 of 2500 molecules bound/cell is considered to have diagnostic value for sepsis in adults, with a sensitivity of 94.1% [7]. P.C.…”
Section: Discussionmentioning
confidence: 99%